Influencia del tipo y dosificación de almidones naturales obtenidos de yuca blanca, plátano verde y papa amarilla, sobre el grado de turbidez en agua de riego de la Empresa Agualima, mediante el proceso de coagulación - floculación - Vasquez Torres, Breidy Tatiana (2019)
In the present research the influence of the type and dosage of natural starches obtained from white cassava, green banana and yellow potato, on the turbidity degree, in irrigation water of the company Agualima, through the coagulation flocculation process was evaluated For the investigation, irrigation water from the company AGUALIMA S.A.C was used, in addition white cassava, green plantain and yellow potatoes from the region were used, and the obtained powder was sieved to a particle size of approximately 0.149 mm. The natural starch was obtained by cutting the tuber, liquefying it and letting it settle in refrigeration at a temperature of 4ºC for three days, every day the swimming envelope was eliminated and more water was placed stirring it to homogenize the sample, this procedure was repeated for three days, then the sedimentation was centrifuged, to eliminate the greater amount of liquid matter, later it was placed in a stove, and finally in a mortar it was crushed and sieved through the Nº 100. The results indicate that the turbidity degree minimun was achieved with the natural starch obtained from white cassava, starting from an initial turbidity of 86.8 NTU up to a turbidity of 13.3 NTU after using cassava starch. The elaborated statistical analysis shows that the type and dosage of natural starch significantly affects the degree of turbidity.